PENGARUH TERAPI HYPNOBREASTFEEDING TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU POSTPARTUM DI WILAYAH KERJA PUSKESMAS REJOSARI PEKANBARU - Andini, Andini; Carles, Carles; Winda Sari, Sabtria; Wulan Ramadhani, Dyah (Ensiklopedia of Journal, 2024)
Breast milk (ASI) is a liquid that has a complete and diverse nutritional content. Hypnobreastfeeding is a relaxation technique to help mothers in the breastfeeding process, by giving positive affirmations / suggestions so that mothers become more relaxed, relaxed and calm in the breastfeeding process. Hypnobreastfeeding technique also referred to as relaxation therapy, this therapy has been suggested as one way to help overcome these obstacles and provide comfort so that the breastfeeding process can run smoothly. This research is a type of Experimental Quasy research, which is an experimental activity that aims to determine a symptom or influence caused before being given Hypnobreastfeeding therapy obtained an average value of 35.00, while after being given Hypnobreastfeeding therapy obtained an average value of 60.00. Non-parametric Wilcoxon test results p-value 0.000 because the value of 0.000 is smaller than 0.05The results of this study are expected to be used as basic data in the development of further research. Researchers suggest conducting research on maternal perception, the importance of exclusively breastfeeding the baby.Keywords: Hypnobreastfeeding, Milk Production, Breastfeeding